Ni-Cu / silicon dioxide catalyst for preparing furfural as well as preparation method and application of Ni-Cu / silicon dioxide catalyst
By preparing Ni-Cu/silica catalyst, the problems of precious metal scarcity and safety risks of external hydrogen sources were solved, and the efficient conversion of hemicellulose into furfural was achieved. The catalyst has high-efficiency and low-consumption hydrothermal catalytic performance.
Patent Information
- Application Number
- CN202510821340.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-09-19
AI Technical Summary
In the existing technology, precious metal catalysts are scarce and unstable, and external hydrogen sources pose safety risks, which hinder the commercialization of the catalytic hydrogenolysis of hemicellulose into furfural.
A Ni-Cu/silica catalyst is prepared by mixing nickel salt, copper salt and silica, and then subjected to ultrasound, water bath, drying and reduction treatment to achieve a method for efficiently converting hemicellulose into furfural.
Without the use of an external hydrogen source, the combination of nickel and copper in the catalyst improves the catalytic performance and achieves efficient and low-consumption directional conversion of hemicellulose to furfural. The metal load on the catalyst surface is uniform, the activity is high, and it has good hydrothermal stability.
Smart Images

Figure CN120662316A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a Ni-Cu / silicon dioxide catalyst for preparing furfural, a preparation method thereof, and applications thereof. Background Art
[0002] Due to the increasing depletion of fossil resources and the resulting environmental problems, the development and utilization of renewable energy sources has attracted increasing attention. In recent years, to reduce dependence on fossil feedstocks, the conversion of renewable biomass into high-value-added chemicals through chemical or biological pathways has attracted widespread attention within the industry. Lignocellulosic biomass is the most abundant natural renewable organic carbon resource and a complex mixture composed of three main components: cellulose (40-50%), hemicellulose (20-35%), and lignin (20-40%). Hemicellulose, a polysaccharide composed of glucose and pentoses (xylose, mannose, galactose, rhamnose, and arabinose), accounts for 20-35% of lignocellulosic biomass. Hemicellulose, with its rich polysaccharide content and excellent physical and chemical properties, is widely used in the production of various materials (emulsifiers, films, hydrogels, etc.) and fine chemicals (xylitol, ethanol, furfural, etc.), as well as in the food, medical, and energy storage industries.
[0003] Furfural, a linker compound in the furan platform, serves as a bridge between biomass and fossil-based industries. It can be derived from numerous downstream chemicals and used as a precursor for liquid fuels. Currently, catalytic hydrogenolysis, a highly efficient carbon atom-utilizing method for the conversion of hemicellulose to furfural, has attracted considerable attention.
[0004] Currently, the core process for catalytic hydrogenolysis of hemicellulose to furfural relies on the use of catalysts and an external hydrogen source. However, factors such as the natural scarcity and high price of precious metals and catalyst instability have hindered large-scale commercialization. Furthermore, the significant safety risks associated with the storage and transportation of external hydrogen sources have limited the development of this process.
[0005] Therefore, how to construct an adaptive non-precious metal-based high-efficiency catalyst without using an external hydrogen source to achieve the efficient conversion of hemicellulose into furfural by catalytic hydrogenolysis is a difficult problem that needs to be solved urgently in this field. Summary of the Invention
[0006] The present invention provides a Ni-Cu / silicon dioxide catalyst for preparing furfural, a preparation method thereof, and an application thereof, which can realize the efficient conversion of hemicellulose into furfural by catalytic hydrogenolysis without using an external hydrogen source.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] A method for preparing a Ni-Cu / silicon dioxide catalyst for preparing furfural comprises the following steps:
[0009] 1) mixing nickel salt, copper salt and water to obtain a nickel-copper bimetallic salt solution;
[0010] 2) mixing the nickel-copper bimetallic salt solution with silicon dioxide, and sequentially performing ultrasonic treatment, water bath treatment, drying, and calcination to obtain bimetallic oxide-loaded silicon dioxide;
[0011] 3) Under a reducing atmosphere, subjecting the bimetallic oxide-loaded silica to a reduction reaction to obtain a Ni-Cu / silicon dioxide catalyst for preparing furfural.
[0012] Preferably, the molar ratio of nickel in the nickel salt, copper in the copper salt and water in step 1) is 0.01-0.04:0.01-0.04:1-8;
[0013] The mixing temperature is 60-80° C., and the mixing time is 30-60 minutes.
[0014] Preferably, the molar ratio of copper ions to silicon dioxide in the nickel-copper bimetallic salt solution in step 2) is 0.01-0.04:0.12-0.16.
[0015] Preferably, the ultrasonic power in step 2) is 200-400W, the temperature is 40-60°C, and the time is 0.5-1.5h;
[0016] The temperature of the water bath is 30-50° C., and the time is 30-50 minutes.
[0017] Preferably, the drying temperature in step 2) is 100-120° C. and the drying time is 8-12 hours;
[0018] The calcination temperature is 400-600° C., and the calcination time is 2-6 hours.
[0019] Preferably, the reducing atmosphere in step 3) comprises a hydrogen atmosphere, and the flow rate of the hydrogen is 80 to 100 mL / min.
[0020] Preferably, the temperature of the reduction reaction in step 3) is 350-500° C., and the time is 1.5-2.5 h.
[0021] Another object of the present invention is to provide a Ni-Cu / silicon dioxide catalyst prepared by the preparation method for preparing furfural.
[0022] Another object of the present invention is to provide an application of the Ni-Cu / silicon dioxide catalyst in catalyzing the conversion of hemicellulose to produce furfural.
[0023] Preferably, the application method comprises:
[0024] A Ni-Cu / silica catalyst, hemicellulose and water are mixed and subjected to a hydrothermal reaction to obtain furfural;
[0025] The mass volume ratio of the Ni-Cu / silicon dioxide catalyst, hemicellulose and water is 0.2-0.8 g: 2-8 g: 20-80 mL;
[0026] The temperature of the hydrothermal reaction is 140-240° C., and the time is 30-180 minutes.
[0027] It can be seen from the above technical solutions that compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention provides a method for preparing a Ni-Cu / silica catalyst for preparing furfural. The method comprises first preparing SiO2 loaded with NiO, CuO, and Cu2O (impurities are generated by the incomplete calcination process) by an impregnation method, and then performing a reduction treatment in a reducing atmosphere to prepare Ni-Cu / silica bimetallic particles. In the Ni-Cu / silica bimetallic particles prepared by the present invention, nickel and copper are combined and loaded on silica, so that a strong metal-support interaction anchors the Ni and Cu nanoparticles, significantly improving the catalytic performance and realizing a multifunctional catalyst. The Ni group has a strong hydrogenation ability, activates H molecules, promotes the hydrogenation saturation of C=O and C=C bonds, and reduces condensation byproducts. The Cu group has a high CO bond cleavage ability, and directionally deoxidizes to produce furfural, inhibiting excessive hydrogenation. The acidic sites on the surface of the SiO2 carrier assist in the initial hydrolysis of xylan (breaking the C-O-C bond), and it is thermally stable: resistant to high-temperature hydrothermal environments, it can maintain the stability of the catalyst structure. The combination of silica-supported nickel and copper enables a strong metal-support interaction to anchor the Ni and Cu nanoparticles, significantly improving catalytic performance and achieving multifunctional catalysis. Therefore, the Ni-Cu / silica bimetallic particles prepared by the present invention have a uniform metal loading on the surface, highly dispersed active components, high activity, and good hydrothermal catalytic performance, which can achieve the targeted conversion of hemicellulose to furfural under efficient and low-consumption reaction conditions.
[0029] The raw material preparation cost of the present invention is low, the method is relatively simple, and it is convenient for large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are merely embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the provided drawings without paying any creative work.
[0031] Figure 1 Schematic diagram of the temperature-programmed reduction test results of the Ni-Cu / SiO2 bimetallic particles prepared in Example 1 (Temperature, Intensity);
[0032] Figure 2 The scanning electron microscope images of the products obtained in Example 1 and Comparative Examples 1-2 are shown; wherein, Figure 2 a is a scanning electron microscope image of Ni / SiO2 of Comparative Example 1 at a scale of 30 μm; Figure 2 b is a scanning electron microscope image of Ni-Cu / SiO2 of Example 1 at a scale of 30 μm; Figure 2 c is a scanning electron microscope characterization image of Cu / SiO2 of comparative example 2 at a scale of 30 μm;
[0033] Figure 3 XRD patterns (Intensity) of the Ni-Cu / SiO2 bimetallic particles prepared in Example 1, the Ni / SiO2 metal nanoparticles in Comparative Example 1, and the Cu / SiO2 metal nanoparticles in Comparative Example 2;
[0034] Figure 4 The selectivity diagram (Selecyivity-selectivity) of furfural prepared by hydrothermal conversion of hemicellulose in Application Example 1 and Comparative Application Examples 1-3. DETAILED DESCRIPTION
[0035] The present invention provides a method for preparing a Ni-Cu / silicon dioxide catalyst for preparing furfural, comprising the following steps:
[0036] 1) mixing nickel salt, copper salt and water to obtain a nickel-copper bimetallic salt solution;
[0037] 2) mixing the nickel-copper bimetallic salt solution with silicon dioxide, and sequentially performing ultrasonic treatment, water bath treatment, drying, and calcination to obtain bimetallic oxide-loaded silicon dioxide;
[0038] 3) Under a reducing atmosphere, subjecting the bimetallic oxide-loaded silica to a reduction reaction to obtain a Ni-Cu / silicon dioxide catalyst for preparing furfural.
[0039] In the present invention, the molar ratio of nickel in the nickel salt, copper in the copper salt and water in step 1) is 0.01-0.04:0.01-0.04:1-8, preferably 0.02-0.03:0.02-0.03:2-6, more preferably 0.024-0.026:0.024-0.026:4-5, and more preferably 0.025:0.024:4.4.
[0040] In the present invention, the nickel salt includes one or more of nickel nitrate, nickel sulfate and nickel chloride; the copper salt includes one or more of copper nitrate, copper sulfate and copper chloride; the nickel salt and copper salt independently also include hydrates corresponding to the salts.
[0041] In the present invention, the mixing temperature is 60-80°C, specifically 62°C, 65°C, 68°C, 70°C, 72°C, 75°C, 78°C; the mixing time is 30-60min, specifically 35min, 40min, 45min, 50min, 55min.
[0042] In the present invention, water and nickel salt are preferably first mixed uniformly, stirred, and the nickel salt is hydrolyzed until the solution is transparent to obtain a first solution; then copper salt is added to the first solution, and stirred to hydrolyze the iron salt until the solution is transparent to obtain a nickel-copper bimetallic salt solution.
[0043] In the present invention, the molar ratio of copper ions to silicon dioxide in the nickel-copper bimetallic salt solution in step 2) is 0.01-0.04:0.12-0.16, preferably 0.02-0.03:0.13-0.15, and more preferably 0.024:0.14.
[0044] In the present invention, the power of the ultrasound in step 3) is 200-400 W, specifically 220 W, 240 W, 250 W, 260 W, 280 W, 300 W, 320 W, 340 W, 350 W, 360 W, and 380 W; the temperature is 40-60 ° C, specifically 42 ° C, 45 ° C, 48 ° C, 50 ° C, 52 ° C, 55 ° C, and 58 ° C; the time is 0.5-1.5 h, specifically 0.6 h, 0.8 h, 1 h, 1.2 h, and 1.4 h; the present invention uses ultrasound to fully mix the silicon dioxide and the nickel-copper bimetallic salt solution.
[0045] In the present invention, the temperature of the water bath is 30-50° C., specifically 32° C., 34° C., 35° C., 36° C., 38° C., 40° C., 42° C., 45° C., or 48° C.; the time is 30-50 min, specifically 32 min., 34 min., 35 min., 36 min., 38 min., 40 min., 42 min., 45 min., or 48 min. In the present invention, water in the solution is evaporated to dryness by water bathing.
[0046] In the present invention, the drying temperature is 100-120°C, specifically 102°C, 105°C, 108°C, 110°C, 112°C, 115°C, 118°C; the drying time is 8-12h, specifically 8.5h, 9h, 9.5h, 10h, 10.5h, 11h, 11.5h.
[0047] In the present invention, the calcination temperature is 400-600°C, specifically 420°C, 450°C, 480°C, 500°C, 520°C, 540°C, 550°C, 560°C, 580°C; the calcination time is 2-6h, specifically 3h, 4h, 5h, 6h.
[0048] In the present invention, the reducing atmosphere in step 3) includes a hydrogen atmosphere, and the flow rate of the hydrogen is 80 to 100 mL / min, specifically 82 mL / min, 84 mL / min, 85 mL / min, 86 mL / min, 88 mL / min, 90 mL / min, 92 mL / min, 94 mL / min, 95 mL / min, 96 mL / min, and 98 mL / min.
[0049] In the present invention, the temperature of the reduction reaction in step 3) is 350-500°C, specifically 360°C, 380°C, 400°C, 420°C, 440°C, 450°C, 460°C, 480°C; the time is 1.5-2.5h, specifically 1.6h, 1.8h, 2h, 2.2h, 2.4h.
[0050] The present invention also provides a Ni-Cu / silicon dioxide catalyst for preparing furfural, prepared by the above-mentioned preparation method. The Ni-Cu / silicon dioxide catalyst of the present invention has a SiO2 mass fraction of 70.56 to 90.42%, more preferably 85%, a Ni mass fraction of 4.77 to 21.8%, more preferably 7.5%, and a Cu mass fraction of 2.31 to 20.96%, more preferably 7.5%.
[0051] The present invention also provides an application of the Ni-Cu / silicon dioxide catalyst in catalyzing the conversion of hemicellulose to prepare furfural.
[0052] In the present invention, the application method comprises: mixing a Ni-Cu / silicon dioxide catalyst, hemicellulose and water, and performing a hydrothermal reaction to obtain furfural.
[0053] In the present invention, the mass volume ratio of the Ni-Cu / silica catalyst, hemicellulose and water is 0.2-0.8g:2-8g:20-80mL, preferably 0.4-0.6g:4-6g:40-60mL, and more preferably 0.5g:5g:50mL.
[0054] In the present invention, the temperature of the hydrothermal reaction is 140-240°C, specifically 150°C, 160°C, 180°C, 200°C, 220°C, and 230°C; the time is 30-180 min, specifically 40 min, 50 min, 60 min, 80 min, 100 min, 120 min, 140 min, 150 min, and 160 min.
[0055] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making any creative efforts are within the scope of protection of the present invention.
[0056] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.
[0057] Example 1
[0058] 80 mL of water and 0.025 mol of nickel nitrate hexahydrate were stirred and mixed uniformly, and the nickel nitrate hexahydrate was mixed at 70° C. until the solution became transparent to obtain a first solution; 0.024 mol of copper nitrate trihydrate was added to the first solution at the above temperature, and the copper nitrate trihydrate was stirred and mixed until the solution became transparent, with a total mixing time of 45 minutes, to obtain a nickel-copper bimetallic salt solution (molar ratio of water, nickel nitrate hexahydrate, and copper nitrate trihydrate was 4.4:0.025:0.024);
[0059] 0.14 mol of silicon dioxide (molar ratio of copper nitrate trihydrate to silicon dioxide: 0.024:0.14) was added to the nickel-copper bimetallic salt solution and stirred to obtain a composite solution; the obtained composite solution was ultrasonicated at 50°C and 300W for 1 hour, then placed in a water bath at 40°C for 40 minutes, then dried at 105°C for 8 hours, and then calcined at 500°C for 2 hours to obtain bimetallic oxide-loaded SiO2;
[0060] Under a hydrogen atmosphere, the bimetallic oxide-loaded SiO2 was subjected to a reduction reaction with a hydrogen flow rate of 90 mL / min, a reduction reaction temperature of 500°C, and a reduction reaction time of 2 h to obtain Ni-Cu / SiO2 bimetallic particles (denoted as Ni-Cu / SiO2), namely the Ni-Cu / silica catalyst used to prepare furfural.
[0061] Comparative Example 1
[0062] The water and nickel nitrate hexahydrate were mixed evenly and stirred thoroughly to mix the nickel nitrate hexahydrate (the volume of water was 80 mL) to obtain a nickel salt solution (the molar ratio of water to nickel nitrate hexahydrate was 4.4:0.025); silicon dioxide was then added to the nickel salt solution (the molar ratio of water, nickel nitrate hexahydrate and silicon dioxide was 4.4:0.025:0.14) and stirred thoroughly to obtain a composite solution; the obtained composite solution was then ultrasonicated at 50°C and 300W for 1 hour, then placed in a water bath at 40°C for 40 minutes, then dried at 105°C for 8 hours, and finally calcined at 500°C for 2 hours to obtain SiO2 loaded with NiO;
[0063] Under a hydrogen atmosphere, the NiO-loaded SiO2 was subjected to a reduction reaction, with the hydrogen flow rate set to 90 mL / min, the reduction reaction temperature to 500°C, and the reduction time to 2 h, to obtain Ni / SiO2 metal particles (labeled as Ni / SiO2).
[0064] Comparative Example 2
[0065] The water and copper nitrate trihydrate were mixed evenly and stirred thoroughly to mix the copper nitrate trihydrate (the volume of water was 80 mL) to obtain a copper salt solution (the molar ratio of water to copper nitrate trihydrate was 4.4:0.024); silicon dioxide was then added to the copper salt solution (the molar ratio of water, copper nitrate trihydrate and silicon dioxide was 4.4:0.024:0.14) and stirred thoroughly to obtain a composite solution; the obtained composite solution was then ultrasonicated at 50°C and 300W for 1 hour, then in a water bath at 40°C for 40 minutes, then dried at 105°C for 8 hours, and finally calcined at 500°C for 2 hours to obtain SiO2 loaded with CuO and Cu2O;
[0066] Under a hydrogen atmosphere, SiO2 loaded with CuO and Cu2O was reduced by setting the hydrogen flow rate to 90 mL / min, the reduction temperature to 350°C (based on the reduction temperature of copper), and the time to 2 h to obtain Cu / SiO2 metal particles (labeled as Cu / SiO2).
[0067] Characterization and testing
[0068] 1) The Ni-Cu / SiO2 bimetallic particles prepared in Example 1 were subjected to a temperature-programmed reduction test to obtain a schematic diagram of the temperature-programmed reduction test results of NiO, CuO and Cu2O, as shown in FIG. Figure 1 As shown. Figure 1 It can be seen from the figure that Ni shows the reduction peak of NiO at 420-500℃; Cu shows the reduction peaks of CuO and Cu2O at 200-350℃, so Ni-Cu / SiO2 bimetallic particles can be obtained by reducing at 500℃.
[0069] 2) The Ni-Cu / SiO2 bimetallic particles in Example 1 and the Ni / SiO2 and Cu / SiO2 in Comparative Examples 1-2 were characterized by scanning electron microscopy. Figure 2 As shown; Figure 2 a in the figure is a scanning electron microscope characterization image of Ni / SiO2 at a scale of 30 μm; Figure 2 b is the scanning electron microscope characterization image of Ni-Cu / SiO2 at a scale of 30μm; Figure 2 c in the figure is the scanning electron microscope characterization image of Cu / SiO2 at a scale of 30μm; Figure 2 It can be seen that the Ni and Cu bimetallics are very evenly distributed on the surface of the SiO2 support and can interact with active components of different properties.
[0070] 3) The Ni-Cu / SiO2 bimetallic particles prepared in Example 1, the Ni / SiO2 metal particles in Comparative Example 1, and the Cu / SiO2 metal particles in Comparative Example 2 were subjected to XRD characterization to obtain an XRD characterization analysis diagram, as shown in FIG. Figure 3 As shown; Figure 3 The significant diffraction peaks at 21.4°, 22.5° and 23.2° correspond to the reflection crystal planes of silica, respectively, indicating that the physical phase of the silica carrier has not changed during the preparation of Ni-Cu / SiO2 bimetallic particles, and the basic structure has not been destroyed, which is very stable; the significant diffraction peaks at 43.3° and 44.5° correspond to the reflection crystal planes of metallic copper and metallic nickel, respectively, indicating that Cu has been 2+ and Ni 2+ Restoration.
[0071] 4) The Ni-Cu / SiO2 particles prepared in Example 1 and the Ni / SiO2 and Cu / SiO2 particles prepared in Comparative Examples 1 and 2 were characterized by ICP to obtain the property parameters of the different particles, as shown in Table 1.
[0072] Table 1 Property parameters of different metal particles
[0073]
[0074] As can be seen from Table 1, the loading effect of Ni-Cu / SiO2 bimetallic particles is very good during the preparation process, and the ratio of actual loading to theoretical loading is 97.2%, indicating that there is no significant loss or volatilization of Ni and Cu metal precursors during the loading process, the carrier has high adsorption efficiency for metals, and subsequent treatment does not cause the metal to detach from the carrier. The number of active sites is in line with expectations, providing a basis for catalytic performance.
[0075] Application Example 1
[0076] In a hydrothermal reactor, 0.5 g of the Ni-Cu / SiO2 metal particles prepared in Example 1, 5 g of hemicellulose, and 50 mL of water were mixed and subjected to a hydrothermal reaction at 180°C for 120 min to test the bio-oil yield from the hydrothermal liquefaction of hemicellulose.
[0077] Comparative Application Example 1
[0078] The other conditions in Application Example 1 were controlled to remain unchanged, and the Ni-Cu / SiO2 metal particles prepared in Example 1 were not added to test the bio-oil yield from hemicellulose hydrothermal liquefaction.
[0079] Comparative Application Example 2
[0080] The other conditions in Application Example 1 were kept unchanged, and the mass of Ni-Cu / SiO2 metal particles prepared in Example 1 was replaced by the Ni / SiO2 metal particles prepared in Comparative Example 1 to test the bio-oil yield of hemicellulose hydrothermal liquefaction.
[0081] Comparative Application Example 3
[0082] The other conditions in Application Example 1 were kept unchanged, and the mass of the Ni-Cu / SiO2 metal particles prepared in Example 1 was replaced by the Cu / SiO2 metal particles in Comparative Example 2 to test the bio-oil yield from hemicellulose hydrothermal liquefaction.
[0083] Table 2 is obtained based on the test results of the bio-oil yield of hemicellulose hydrothermal liquefaction in Application Example 1 and Comparative Application Examples 1 to 3.
[0084] Table 2 Test results of hemicellulose hydrothermal liquefaction bio-oil
[0085] Case Bio-oil yield (wt%) Application Example 1 10.36 Comparative Application Example 1 4.86 Comparative Application Example 2 13.26 Comparative Application Example 3 7.04
[0086] As can be seen from Table 2, compared with Comparative Application Example 1, the catalyst can always improve the production of hemicellulose hydrothermal liquefaction bio-oil. Ni-Cu / SiO2 metal particles can make the hemicellulose hydrothermal liquefaction bio-oil yield reach 10.36%, which is 5.50% higher than the condition without catalyst in Comparative Application Example 1, indicating that the Ni-Cu / SiO2 metal particles as a catalyst can improve the conversion rate of hemicellulose and increase the bio-oil yield.
[0087] From the test results of furfural selectivity in the products of Application Example 2 and Comparative Application Examples 4 to 6, we can get Figure 4 , where Blank corresponds to comparative application example 1. Figure 4As shown, at 180°C, Ni-Cu / SiO2 metal particles achieve a selectivity of 468.5 mg / g for the hydrothermal conversion of hemicellulose to furfural, an increase of 427.9 mg / g compared to the catalyst-free conditions in Comparative Application Example 4. This represents increases of 289.5 mg / g and 196.6 mg / g compared to the conditions with Ni / SiO2 and Cu / SiO2 metal particles, respectively, demonstrating the excellent hydrothermal catalytic performance of Ni-Cu / SiO2 metal particles. The bio-oil yield in Comparative Application Example 2 is higher than that in Application Example 1, but the selectivity for the target product, furfural, is lower than that in Application Example 1. This is because the introduction of Cu into the bimetallic catalyst may alter the catalytic properties of Ni through charge or geometric effects. This modification makes the catalyst more inclined to promote the reaction of the target product, furfural, while suppressing excessive hydrogenation or condensation reactions of furfural, thereby improving selectivity. The high hydrogenation activity of monometallic Ni, on the other hand, leads to further reactions of furfural, reducing its selectivity but boosting the overall bio-oil yield. The above results show that under the condition of a temperature of 180°C, the Ni-Cu / SiO2 metal particles prepared by the present invention can achieve in situ hydrogen production from subcritical water through a "one-pot method", promoting the hydrogenation and deoxygenation process of hemicellulose. Ni dominates H activation and hydrogenation saturation, while Cu dominates CO bond cleavage and deoxygenation. At the same time, the SiO2 carrier surface provides acidic sites; the Ni-Cu interface optimizes the electronic structure, realizing the directional conversion of hemicellulose to furfural under mild reaction conditions.
[0088] Example 2
[0089] 144 mL of water and 0.04 mol of nickel nitrate hexahydrate were stirred and mixed uniformly, and the nickel nitrate hexahydrate was mixed at 60° C. until the solution became transparent to obtain a first solution; 0.04 mol of copper nitrate trihydrate was added to the first solution at the above temperature, and the copper nitrate trihydrate was stirred and mixed until the solution became transparent, with a total mixing time of 60 minutes, to obtain a nickel-copper bimetallic salt solution (molar ratio of water, nickel nitrate hexahydrate, and copper nitrate trihydrate: 8:0.04:0.04);
[0090] 0.16 mol of silicon dioxide (molar ratio of copper nitrate trihydrate to silicon dioxide: 0.04:0.16) was added to the nickel-copper bimetallic salt solution and stirred to obtain a composite solution; the obtained composite solution was ultrasonicated at 40°C and 300W for 0.5 h, then placed in a water bath at 30°C for 50 min, then dried at 105°C for 12 h, and then calcined at 600°C for 3 h to obtain bimetallic oxide-loaded SiO2;
[0091] Under a hydrogen atmosphere, the bimetallic oxide-loaded SiO2 was subjected to a reduction reaction with a hydrogen flow rate of 100 mL / min, a reduction reaction temperature of 400°C, and a reduction reaction time of 2 h to obtain Ni-Cu / SiO2 bimetallic particles, namely the Ni-Cu / silica catalyst for the preparation of furfural.
[0092] Example 3
[0093] 18 mL of water and 0.01 mol of nickel nitrate hexahydrate were stirred and mixed uniformly, and the nickel nitrate hexahydrate was mixed at 80° C. until the solution became transparent to obtain a first solution; 0.02 mol of copper nitrate trihydrate was added to the first solution at the above temperature, and the copper nitrate trihydrate was stirred and mixed until the solution became transparent, with a total mixing time of 35 minutes, to obtain a nickel-copper bimetallic salt solution (molar ratio of water, nickel nitrate hexahydrate, and copper nitrate trihydrate was 1:0.01:0.02);
[0094] 0.12 mol of silicon dioxide (molar ratio of copper nitrate trihydrate to silicon dioxide: 0.02:0.12) was added to the nickel-copper bimetallic salt solution, and stirred to obtain a composite solution; the obtained composite solution was ultrasonicated at 60°C and 300W for 1 hour, then placed in a water bath at 45°C for 30 minutes, then dried at 120°C for 10 hours, and then calcined at 400°C for 5 hours to obtain bimetallic oxide-loaded SiO2;
[0095] Under a hydrogen atmosphere, the bimetallic oxide-loaded SiO2 was subjected to a reduction reaction with a hydrogen flow rate of 100 mL / min, a reduction reaction temperature of 350°C, and a reduction reaction time of 2.5 h to obtain Ni-Cu / SiO2 bimetallic particles (denoted as Ni-Cu / SiO2), namely the Ni-Cu / silica catalyst used to prepare furfural.
[0096] As can be seen from the above examples, the present invention first adopts an impregnation method to prepare bimetallic oxide-loaded SiO2, and then adopts a reduction treatment method to prepare Ni-Cu / SiO2 bimetallic particles. The active components in the catalyst are highly dispersed, and it has excellent hydrothermal catalytic performance. It can achieve in situ hydrogen production in subcritical water and promote the hydrogenation and deoxygenation process of hemicellulose. Ni dominates H activation and hydrogenation saturation, and Cu dominates CO bond breaking and deoxygenation. At the same time, the surface of the SiO2 carrier provides dispersion sites, an acidic environment and mass transfer channels; the Ni-Cu interface optimizes the electronic structure, realizing the directional conversion of hemicellulose to furfural under mild reaction conditions.
[0097] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.
[0098] The above description of the disclosed embodiments is intended to enable one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be readily apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention is not limited to the embodiments shown herein but is intended to conform to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A method for preparing a Ni-Cu / silicon dioxide catalyst for preparing furfural, characterized in that: The following steps are involved: 1) mixing nickel salt, copper salt and water to obtain a nickel-copper bimetallic salt solution; 2) mixing the nickel-copper bimetallic salt solution with silicon dioxide, and sequentially performing ultrasonic treatment, water bath treatment, drying, and calcination to obtain bimetallic oxide-loaded silicon dioxide; 3) Under a reducing atmosphere, subjecting the bimetallic oxide-loaded silica to a reduction reaction to obtain a Ni-Cu / silicon dioxide catalyst for preparing furfural.
2. The method for preparing a Ni-Cu / silicon dioxide catalyst for preparing furfural according to claim 1, wherein The molar ratio of nickel in the nickel salt, copper in the copper salt and water in step 1) is 0.01-0.04:0.01-0.04:1-8; The mixing temperature is 60-80° C., and the mixing time is 30-60 minutes.
3. The method for preparing the Ni-Cu / silicon dioxide catalyst for preparing furfural according to claim 2, wherein The molar ratio of copper ions to silicon dioxide in the nickel-copper bimetallic salt solution in step 2) is 0.01-0.04:0.12-0.
16.
4. The method for preparing a Ni-Cu / silicon dioxide catalyst for preparing furfural according to any one of claims 1 to 3, characterized in that: The ultrasonic power in step 2) is 200-400W, the temperature is 40-60°C, and the time is 0.5-1.5h; The temperature of the water bath is 30-50° C., and the time is 30-50 minutes.
5. The method for preparing the Ni-Cu / silicon dioxide catalyst for preparing furfural according to claim 4, wherein: The drying temperature in step 2) is 100-120° C. and the drying time is 8-12 hours; The calcination temperature is 400-600° C., and the calcination time is 2-6 hours.
6. The method for preparing the Ni-Cu / silicon dioxide catalyst for preparing furfural according to claim 5, wherein: The reducing atmosphere in step 3) includes a hydrogen atmosphere, and the flow rate of the hydrogen is 80 to 100 mL / min.
7. The method for preparing the Ni-Cu / silicon dioxide catalyst for preparing furfural according to claim 5 or 6, characterized in that: The temperature of the reduction reaction in step 3) is 350-500° C., and the time is 1.5-2.5 h.
8. A Ni-Cu / silicon dioxide catalyst for preparing furfural prepared by the preparation method according to any one of claims 1 to 7.
9. Use of the Ni-Cu / silicon dioxide catalyst according to claim 8 in catalyzing the conversion of hemicellulose to produce furfural.
10. Use of the Ni-Cu / silicon dioxide catalyst according to claim 9 in catalyzing the conversion of hemicellulose to produce furfural, characterized in that: The method of application includes: A Ni-Cu / silica catalyst, hemicellulose and water are mixed and subjected to a hydrothermal reaction to obtain furfural; The mass volume ratio of the Ni-Cu / silicon dioxide catalyst, hemicellulose and water is 0.2-0.8 g: 2-8 g: 20-80 mL; The temperature of the hydrothermal reaction is 140-240° C., and the time is 30-180 minutes.